EFEKTIVITAS PELATIHAN LIFE SKILL TERHADAP PENGETAHUAN DAN SIKAP TENTANG KESEHATAN REPRODUKSI REMAJA - Winarti, Eko; Anggi Umbu Pingge, Yusti; Alimansur, Moh; Agung Mirasa, Yudied (coba, 2024)
The level of knowledge of adolescents regarding reproductive health in Indonesia is still relatively low. Survey results show that many teenagers do not understand the function of reproductive organs, the risk of sexually transmitted diseases, and the importance of family planning. This research aims to determine the effectiveness of life skills training on knowledge and attitudes about adolescent reproductive health. The type of research used in this research uses quantitative methods with a pre-experimental design with a one-group pretest post test design. The population in this study were all teenagers in SMK "Y" class X. The sample of teenagers in SMK "Y" Surabaya class X was 40 respondents. The sampling technique uses cluster random sampling. Statistical analysis in this study was carried out using the Wilcoxon signed rank test. The results of the training intervention can influence the increase in teenagers' knowledge and attitudes about teenage reproductive health life skills at SMK "Y", so it can be concluded that the training provided is effective in increasing teenagers' knowledge and attitudes about teenage reproductive health life skills. It is hoped that the school will provide educational training about reproductive health to adolescents from an early age.